2018
DOI: 10.1653/024.101.0333
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Phytomyza orobanchia (Diptera: Agromyzidae) from Poland and Chymomyza amoena (Diptera: Drosophilidae) on Phelipanche ramosa (Orobanchaceae)

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…In line with the findings obtained in the current study, Piwowarczyk et al (2018) reported that the infestation of Phelipanche ramosa by P. orobanchia in tomato crops was observed in the form of mining in flowers (ovary with seeds), shoots, and tubers. A single broomrape plant could be parasitized by 1 to 10 larvae.…”
Section: -Efficiency Of Phytomyza Orobanchia As a Bio-agent On The Egyptian Broomrape Phelipanche Aegyptiacasupporting
confidence: 93%
“…In line with the findings obtained in the current study, Piwowarczyk et al (2018) reported that the infestation of Phelipanche ramosa by P. orobanchia in tomato crops was observed in the form of mining in flowers (ovary with seeds), shoots, and tubers. A single broomrape plant could be parasitized by 1 to 10 larvae.…”
Section: -Efficiency Of Phytomyza Orobanchia As a Bio-agent On The Egyptian Broomrape Phelipanche Aegyptiacasupporting
confidence: 93%
“…P. ramosa is one of the most important root parasites in agriculture. Expansiveness of P. ramosa resulted from producing large quantities of long-living seeds (Joel et al, 2007; Piwowarczyk et al, 2018). Endophytes may be one of the factors promoting seed viability and germination (Truyens et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, data show that this bacteria occurs in insect gut and can be a novel entomopathogen of Anomala dimidiata and Holotrichia longipennis (Scarabaeidae: Coleoptera) (Selvakumar et al, 2011). This is notable with respect to entomopathogenic potential because P. ramosa is attacked by the monophagous fly Phytomyza orobanchia (Diptera: Agromyzidae), whose larvae can reduce seed production by 30–90%, and this is the most effective biological control agent of broomrape (Klein and Kroschel, 2002; Piwowarczyk et al, 2018). It is possible that this bacteria could be transferred by seeds of P. ramosa to P. orobanchia larvae or other insects during the feeding process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation